(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The present state of Archaeo–Iberian Philology, which we consider rather worrying in some respects, encourages us to formulate a series of considerations about the methodology and procedures of this growing discipline.